The immune system in the elderly: III. Innate Immunity - Ginaldi, L.; Martinis, M. De; D’Ostilio, A.; Marini, L.; Loreto, M. F.; Quaglino, D. (Immunologic research, 1999)
The capability to cope with infectious agents and cancer cells resides not only in adaptive immune responses against specific antigens, mediated by T and B lymphocytes clonally distributed, but also in natural immune reactions. These innate defence mechanisms include chemotaxis, phagocytosis, natural cytotoxicity, cell interactions, and soluble mediators or cytokines. However, specific and natural immune mechanisms are always closely linked and interconnected, providing the primary defense against pathogens. The Authors discuss the main changes observed with advancing age in granulocytes and natural killer (NK) cell activity, in the expression and function of adhesion molecules, and in the pattern of cytokine production. Since phagocytic function is the primary mechanism through which the immune system eliminates most extracellular pathogenic microorganisms, analysis of this function is of clinical importance. Neutrophils from aged subjects often exhibit a diminished phagocytic capacity, as well as a depressed respiratory burst, notwithstanding an activated state. The activity of NK cells during aging has been studied extensively and different results have been reported. The most consistent data indicate an increase in cells with high NK activity with advancing age. Cells from healthy centenarians can efficiently kill target cells. This finding seems to suggest that innate immunity and in particular NK cell activity, is not heavily deteriorated with age. Conversely, a low NK activity is a predictor of impending morbidity. Immunosenescence is associated with increased expression of several cell adhesion molecules (CAM) resulting in an augmented capacity to adhere. Finally, also the cytokine network, responsible for differentiation, proliferation, and survival of lymphoid cells, undergoes complex changes with age. The main findings are a Th1 to Th2 cytokine production shift and an increased production of proinflammatory cytokines, which could explain many aspects of age-associated pathological events, such as atherosclerosis and osteoporosis.